Graduation performances Phygital Glitch & Run/through - Tiffany Margelin 1998- (2022)
Iceland University of the Arts Performing arts department Contemporary Dance, graduation show Performed in L223, Laugarnesi, May 12.-15. 2022 Dagana 12.-15. maí sýna nemendur á alþjóðlegri samtímadansbraut útskriftarverk sín. Flutt verða tvö ný dansverk eftir Katrínu Gunnarsdóttur og Gígju Jónsdóttur unnin sérstaklega fyrir útskriftarbekkinn. May 12th - 15th the Contemporary Dance department graduating class will perform their graduation show, two original works by choreographers Katrín Gunnarsdóttir and Gígja Jónsdóttir. Ávarp fagstjóra Dear guests A dancer's graduation performance marks both a beginning and an end. It is a rite of passage, concluding their time together as students while entering the professional community as dance artists. In this double-bill performance, we witness ten graduating students of Contemporary Dance Practices taking on rituals of the past and future. Embodying landscapes with playful encounters as instruments, thinkers, bodies, avatars, oracles. During their three-year BA education at the Iceland University of the Arts, these emerging dance artists have shown such resilience and passion in challenging circumstances during the pandemic. I welcome you to celebrate their unique artistry and dedication to their craft as they dance - with open hearts, shaking the ground, making us listen. They have arrived. Katrín Gunnarsdóttir Associate Professor and Programme Director Graduating students // Birna Karlsdóttir Gabriel Marling Rideout Inga María Olsen Jóna Hlín Elíasdóttir Lena Margrét Jónsdóttir Marikki Nyfors Ragnhildur Birta Ásmundsdóttir Rebekka Sól Þórarinsdóttir Sóley Ólafsdóttir Tiffany Margelin Phygital Glitch Phygital Glitch Dwelling somewhere in between, facing the forest gaze and playground maze inside an outlined space. Collective force and external source moving through the course of time. Original music by Örlygur Steinar Arnalds graduating from B.A. Music. PSA. Strobe lights are used in the show. Choreography // Gígja Jónsdóttir in collaboration with the performers ...